Optimalisasi Pemberdayaan Masyarakat Desa Peri-Urban melalui Penguatan Kapasitas Sosial, Ekonomi, dan Lingkungan - Wahyumi Ekawanti; Indah Rahayu Lestari; Rachmat Arief; Qodariah Qodariah; Syaiful Anwar; Setyani Dwi Lestari (JPM: Jurnal Pengabdian Masyarakat, 2026)
The Village Government of Mekarwangi (Cisauk District, Tangerang Regency), acting as the community service partner, faces challenges in managing a peri-urban area undergoing rapid urbanization. Observations by the service team identified several issues: low levels of household waste utilization and environmental conservation; limited visual identity and competitiveness among MSMEs; suboptimal road safety facilities; and the persistence of bullying in local elementary schools. These conditions highlight the need for an integrated community empowerment initiative to enhance the environmental quality, social capacity, and economic potential of the Mekarwangi community. This service activity aims to optimize community capacity through a participatory, educational, collaborative, and empowerment-oriented approach, actively involving the village government, schools, MSMEs, and local residents. The initiative’s primary contribution is an integrated empowerment model that combines environmental, social, economic, and infrastructure aspects into programs tailored to the characteristics of a peri-urban village. Implementation involved community education and mentoring, the construction of supporting facilities, and skills training customized to the community's specific needs. Results indicate that all program targets were successfully achieved, including the construction of 10 biopore infiltration holes, the installation of signage systems at three strategic locations, anti-bullying awareness sessions for elementary students, and training on used cooking oil utilization that resulted in the production of 10 aromatherapy candles. Beyond physical outputs, the activity increased community knowledge and awareness regarding environmental conservation, waste management, public facility safety, and the importance of fostering a safe, bullying-free learning environment. Active community participation and village government support demonstrate that the implemented empowerment model strengthens stakeholder collaboration and serves as a foundation for sustainable programs aimed at improving the quality of life for the residents of Mekarwangi as a peri-urban village.